Peptide Reactivity of Isothiocyanates – Implications for Skin Allergy - Karlsson, Isabella (Sci Rep, 2016)
Skin allergy is a chronic condition that affects about 20% of the population of the western world. This disease is caused by small reactive compounds, haptens, able to penetrate into the epidermis and modify endogenous proteins, thereby triggering an immunogenic reaction. Phenyl isothiocyanate (PITC) and ethyl isothiocyanate (EITC) have been suggested to be responsible for allergic skin reactions to chloroprene rubber, the main constituent of wetsuits, orthopedic braces, and many types of sports gear. In the present work we have studied the reactivity of the isothiocyanates PITC, EITC, and tetramethylrhodamine-6-isothiocyanate (6-TRITC) toward peptides under aqueous conditions at physiological pH to gain information about the types of immunogenic complexes these compounds may form in the skin. We found that all three compounds reacted quickly with cysteine moieties. For PITC and 6-TRITC the cysteine adducts decomposed over time, while stable adducts with lysine were formed. These experimental findings were verified by DFT calculations. Our results may suggest that the latter are responsible for allergic reactions to isothiocyanates. The initial adduct formation with cysteine residues may still be of great importance as it prevents hydrolysis and facilitates the transport of isothiocyanates into epidermis where they can form stable immunogenic complexes with lysine-containing proteins.